On the critical $p$-Kirchhoff equation - Hasani, Erisa; Perera, Kanishka (Topological Methods in Nonlinear Analysis, 2023)
We study a nonlocal elliptic equation of $p$-Kirchhoff type involving the critical Sobolev exponent. First we give sufficient conditions for the $(\text{PS})$ condition to hold. Then we prove some existence and multiplicity results using tools from Morse theory, in particular, the notion of a cohomological local splitting and eigenvalues based on the Fadell-Rabinowitz cohomological index.